2001
DOI: 10.1021/bi010902s
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 and Glucagon-like-peptide-1:  NMR Structural Comparisons in the Solution and Micelle-Associated States

Abstract: Exendin-4, a 39 amino acid peptide originally isolated from the oral secretions of the lizard Heloderma suspectum, has been shown to share certain activities with glucagon-like-peptide-1 (GLP-1), a 30 amino acid peptide. We have determined the structuring preferences of exendin-4 and GLP-1 by NMR in both the solution and dodecylphosphocholine (DPC) micelle-associated states. Based on both chemical shift deviations and the pattern of intermediate range NOEs, both peptides display significant helicity from resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
249
2
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(269 citation statements)
references
References 56 publications
14
249
2
4
Order By: Relevance
“…This susceptibility of GLP-1 towards degradation in vivo, compared to peptides that, judged from their sequence and in vitro kinetic data, ought to be cleaved at a similar rate, indicates that, in addition to differences in primary structure, other features such as differences in secondary structure may render GLP-1 particularly prone to cleavage. With regard to exendin-4, it could be speculated that the tertiary structure, formed by the C-terminal extension [25], may help protect it from degradation not only because of the increased size of the peptide (i.e. NEP has a preference for smaller substrates [26]), but also by simply hindering the access of substrate to enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This susceptibility of GLP-1 towards degradation in vivo, compared to peptides that, judged from their sequence and in vitro kinetic data, ought to be cleaved at a similar rate, indicates that, in addition to differences in primary structure, other features such as differences in secondary structure may render GLP-1 particularly prone to cleavage. With regard to exendin-4, it could be speculated that the tertiary structure, formed by the C-terminal extension [25], may help protect it from degradation not only because of the increased size of the peptide (i.e. NEP has a preference for smaller substrates [26]), but also by simply hindering the access of substrate to enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the N termini of GLP-1 and exendin-4 are almost identical, exendin-4 contains 9 extra amino acids at the C terminus, which have been shown by NMR analysis to form a compact folding unit termed a "Trp-cage" (20). The NMR analysis also reveals that the central region of exendin-4 is largely helical, whereas the N terminus is rather more disordered (20).…”
Section: ) For Example In 1964mentioning
confidence: 96%
“…The NMR analysis also reveals that the central region of exendin-4 is largely helical, whereas the N terminus is rather more disordered (20). Although the central region of exendin-4 (comprising residues 10 -30) only shares 8 identical residues with GLP-1, they all lie on the same face of an ideal ␣-helix, suggesting that it is this face of the helix which makes the critical contact with the receptor (21).…”
Section: ) For Example In 1964mentioning
confidence: 96%
“…NMR-study revealed a well-converged helix over residues 18-27 in both GLP-1 and exendin-4 in the conditions mimicking that just prior to binding to the receptor. Exendin-4 was shown to display a greater intrinsic propensity toward the formation of a monomeric helix than GLP-1, which can be attributed to the absence in exendin-4 of the helix-interrupting glycine residue at position 16 of GLP-1 (Neidigh et al, 2001). This allows for the helix to go much further toward the N-terminus in exendin-4 that, along with other structural differences between GLP-1 and exendin-4, may reduce the entropic cost of binding and be responsible for the higher potency of exendin-4 in some organisms.…”
Section: Structurementioning
confidence: 99%
“…Exendin-4 was shown to stimulate secretion of insulin in the presence of elevated blood glucose concentrations, but not during hypoglycemic periods, which led to its pharmacological use in the treatment of type 2 diabetes (Neidigh et al, 2001). Treatment with exendin-4 increases cell proliferation and neuroblast differentiation in the dentate gyrus, potentially through promoting structural plasticity (Li et al, 2010).…”
Section: Functionmentioning
confidence: 99%